A Kinase-Phosphatase Switch Transduces Environmental Information into a Bacterial Cell Cycle Circuit. - Kristina Heinrich; Patrick Sobetzko; Kristina Jonas (PLoS Genetics, 2016)
The bacterial cell cycle has been extensively studied under standard growth conditions. How it is modulated in response to environmental changes remains poorly understood. Here, we demonstrate that the freshwater bacterium Caulobacter crescentus blocks cell division and grows to filamentous cells in response to stress conditions affecting the cell membrane. Our data suggest that stress switches the membrane-bound cell cycle kinase CckA to its phosphatase mode, leading to the rapid dephosphorylation, inactivation and proteolysis of the master cell cycle regulator CtrA. The clearance of CtrA results in downregulation of division and morphogenesis genes and consequently a cell division block. Upon shift to non-stress conditions, cells quickly restart cell division and return to normal cell size. Our data indicate that the temporary inhibition of cell division through the regulated inactivation of CtrA constitutes a growth advantage under stress. Taken together, our work reveals a new mechanism that allows bacteria to alter their mode of proliferation in response to environmental cues by controlling the activity of a master cell cycle transcription factor. Furthermore, our results highlight the role of a bifunctional kinase in this process that integrates the cell cycle with environmental information.